Metanalytical study of the quality of swine wastewater - Maria das Graças Abreu dos Santos; Ana Paula Maia dos Santos (Universidade Estadual de Alagoas, 2021)
Pig farming is considered one of the activities of animal production with great potential for polluting the environment. And possible negative impacts directly related to soil and water, when waste management occurs inappropriately. Wastewater from animal husbandry can be used to increase the production of fodder, reducing the use of drinking water and production costs. The quality of swine wastewater is variable, however, there are still few studies in Brazil that portray the fertilizing potential of these waters. It is essential to know the positive and negative factors of the use of water from swine activities and, above all, the physical-chemical composition of these waters. Thus, the objective was to characterize the quality of wastewater from pig farming through a metanalytical study.